Intra-household dynamics regarding nutritional decisions in rural Guatemala - Twyman, Jennifer; Useche, Pilar; González, Carolina; Talsma, Elise F.; Lopera, Diana Carolina (International Center for Tropical Agriculture, 2018)
The study “His and hers, time and income: How intra-household dynamics impact nutrition in agricultural households” is a research project lead by CIAT and the University of Florida. This project is part of the Innovative Methods and Metrics for Agriculture and Nutrition Actions initiative funded by the UK Department for International Development (DFID) to promote new measures and methodologies for agriculture and food systems to improve health and nutrition. This project includes a multidisciplinary team comprised of agricultural economists, nutritionists and gender specialists.